2007
DOI: 10.1007/s10832-007-9349-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth atmosphere and Ir contamination on electric properties of La3Ta0.5Ga5.5O14 single crystal grown by the floating zone and Czochralski method

Abstract: The influence of growth atmosphere and Ir contamination on electrical resistivity of langatate (La 3 Ta 0.5 Ga 5.5 O 14 ; LTG) was studied. LTG single crystals were grown via the Czochralski method under different oxygen partial pressures with Ir contamination from the Ir crucible. In addition, LTG crystals were grown by the floating zone method and they were not contaminated by Ir. The electrical resistivity and ionic transport number of these crystals were measured in the temperature range 300-1000°C. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…LGT crystals are commonly grown by Czochralski method using an Iridium crucible [5] [6] [10] [15]. Kimura et al [15] reported that LGT crystals contain iridium ions, which are responsible to the crystal color.…”
Section: Metal Ions Impuritiesmentioning
confidence: 99%
See 3 more Smart Citations
“…LGT crystals are commonly grown by Czochralski method using an Iridium crucible [5] [6] [10] [15]. Kimura et al [15] reported that LGT crystals contain iridium ions, which are responsible to the crystal color.…”
Section: Metal Ions Impuritiesmentioning
confidence: 99%
“…Kimura et al [15] reported that LGT crystals contain iridium ions, which are responsible to the crystal color. However, Fs LA-ICP-MS chemical analyses [3] show that iridium concentration in LGT crystals is below 1 ppm.…”
Section: Metal Ions Impuritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ir contamination is considered to be the origin of the coloration in langasite crystals. 4) Therefore, the use of a different crucible for growth is needed in order to elucidate if Ir traces affect the intrinsic properties of CTGS crystals. Furthermore, the influence of oxygen partial pressure during growth on the properties of CTGS has not been investigated so far, mainly due to the use of Ir crucibles, which critically limit the maximum concentration of oxygen to a few percent.…”
Section: Introductionmentioning
confidence: 99%